Factors Relating to Physical Activities of the Elderly in a Village, Bangpla Subdistrict , Bangplee District, Samutprakarn Province - กตัญญุตานนท์ ตวงพร; แป้นสมบุญ ฐานิดา; จินดามณี จันจิรา; รุ่งเรือง พิลัมภา; เกลี้ยงเกลา มณีรัตน์; หอมจันทร์ พรนภา; มอหะ ฟิตตรี; อินทคีรี อิงอร (Journal of Health Sciences and Wellness, 2019)
The objectives of this cross-sectional descriptive research were to study the level of physical activities and to study the relationship of predisposing, reinforcing, and enabling factors with physical activities of the elderly people in a village, Bang Pla Sub-District, Bang Phli District, SamutPrakan Province. The sample was 200 independent elderly people with least 60 years of age in a village, Bang Pla Sub-District, Bang Phli District, SamutPrakan Province and was selected by using the stratified random sampling based on gender, then simple random sampling was used by a lottery. The questionnaire was used as a research tool for data collection. The obtained data were analyzed using frequency, percentage, mean, standard deviation, chi-square test and Spearman’s rank correlation analysis. The results showed that the elderly people were in a moderate level of physical activities. (=2.96, SD=0.78). The predisposing factor was occupation, which had a correlation with the physical activities of the elderly people at a significance level of 0.05 (p-value = 0.002). Alternatively, gender, age, marital status, educational level, and income level had no significant correlation with the physical activities of the elderly people. Knowledge and attitudes about physical activity were positively correlated with physical activity at low and moderate levels at a significance level of 0.01 (r = 0.379, 0.673 p-value = 0.000). The reinforcing factors consisted of family support, which had a low positive correlation with the physical activities at a significance level of 0.01 (r = 0.068, p-value = 0.000). Similarly, support from the village health volunteers and support from the community had a moderate positive correlation with the physical activities of the elderly people at a significance level of 0.01 (r = 0.643, 0.502, p-value = 0.000). The enabling factor of the elderly people was facility, which had a low positive correlation with the physical activities at a significance level of 0.01 (r = 0.378, p-value = 0.000).